1986
DOI: 10.3109/01913128609014592
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Epithelial Cells and Reactive Components in Thymomas: An Ultrastructural and Immunohistochemical Study

Abstract: Fourteen thymomas were studied by electron microscopy and immunohistochemistry. Based on the ultrastructure of the neoplastic epithelial cells in comparison with normal thymic epithelium, four cortical-, three mixed-, five medullary-, and two corpuscular-type tumors were categorized. Histologically the tumors of cortical type showed prominent lymphocytic infiltration, but scant interdigitating reticulum cells (IDCs) were demonstrated by immunoperoxidase method on paraffin sections with anti-S-100 protein antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This swith function from proapoptotic activity to cell-migration and motility-promoting might be correlated with DAP3 overexpression advanced thymoma. Human thymoma is a peculiar epithelial neoplasm where abnormal epithelium supports the differentiation of polyclonal T-lymphocytes [27][28][29][30]. The immunophenotypic studies have shown that most of the lymphocytes in thymoma are identical to normal cortical thymocytes [27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…This swith function from proapoptotic activity to cell-migration and motility-promoting might be correlated with DAP3 overexpression advanced thymoma. Human thymoma is a peculiar epithelial neoplasm where abnormal epithelium supports the differentiation of polyclonal T-lymphocytes [27][28][29][30]. The immunophenotypic studies have shown that most of the lymphocytes in thymoma are identical to normal cortical thymocytes [27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…To date, immunohistochemical studies using various epithelial markers could not detect any definite differences between medullary and cortical type thymomas [4,10,22,25,27,32]. There were only two studies using PE-35 in cryostat sections of thymomas to characterize the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] It has already been demonstrated by conventional histology that thymomas contain lymphocytes with a stimulated or activated appearance, and some mitoses are also seen. [27][28][29] However, in our study, neither mRNA nor protein level of GPI-80 in thymoma correlated with lymphocyte infiltration of thymoma. Thus, we believe that expression of the gene was not correlated with normal lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…20) Human thymoma is a peculiar epithelial neoplasm in which abnormal epithelium supports the differentiation of polyclonal T-lymphocytes. [27][28][29][30] Immunophenotypic studies have shown that most lymphocytes in thymoma are identical to normal cortical thymocytes. [27][28][29] It has already been demonstrated by conventional histology that thymomas contain lymphocytes with a stimulated or activated appearance, and some mitoses are also seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation